Marginalia en "Les deux sources de la morale et la religion" de Henri Bergson - de Salas Ortueta, Jaime; Hormaechea Ocaña, Andrea (Revista de Estudios Orteguianos, 2022)
Marginalia en "Les deux sources de la morale et la religion" de Henri Bergson